A School Nurse Application of the ECHO Model. (August 2021) - Shimasaki, Suzuho; Brunner Nii, Pamela; Davis, Lisa; Bishop, Erin; Berget, Cari; Perreault, Christine; Thomas, John F. "Fred"
Type I diabetes (T1D) is one of the most common childhood diseases and Type 2 diabetes (T2D) is increasing at alarming rates. Given that children spend a great percentage of their time in school, this setting is a critical environment for models of care that lead to better management of this and other health conditions. The School Nurses Managing Diabetes Care ECHO was offered to Colorado school nurses to build their capacity in providing evidence-based management of T1D. The purpose of this effort was to (1) determine whether or not the model could be used as a tool of collaboration and dissemination for school nurses across Colorado and (2) assess the effectiveness of the "School Nurses Managing Diabetes Care" ECHO learning series. Post-series survey results demonstrated a 25% increase in self-efficacy ratings, moving learners from "average among my peers" toward "competent." Additionally, all respondents planned to make one or more practice changes to improve care for students with T1D. Expanding the use of the ECHO model to implement intensive management of children and youth with T1D is critically important as rates of this and other chronic conditions continue to increase.